Material Utilization Technology of Agriculture and Forestry Waste - . Hardoyo (Bandar Lampung University (UBL), 2013)
Indonesia have a large amount of biomass wastes, either species or quantitity. If those biomass were not be treatment will be give some negative environmental impacts. To eliminate the negative impact, the biomass waste must be treatment to produce a new product with higher added value. The material utilization of biomass can mainly be categorized into the utilization of the material applying its own property, the utilization of raw material applying its composition and the utilization of it as fertilizer and feed. Convertion into fertilizer, feed, ligneous plastic, biomass mixing, biodegradable plastic are the kind of material utilizations of agriculture and forest waste